Studies on phytanoyl-CoA 2-hydroxylase and synthesis of phytanoyl-coenzyme A. - Kershaw, N; Mukherji, M; MacKinnon, C; Claridge, T; Odell, B; Wierzbicki, A; Lloyd, MD; Schofield, C (2001)
Phytanoyl-CoA 2-hydroxylase (PAHX), an iron(II) and 2-oxoglutarate-dependent oxygenase, catalyses an essential step in the mammalian metabolism of beta-methylated fatty acids. Phytanoyl-CoA was synthesised and used to develop in vitro assays for PAHX. The product of the reaction was confirmed as 2-hydroxyphytanoyl-CoA by NMR and mass spectrometric analyses. In accord with in vivo analyses, hydroxylation of both 3R and 3S epimers of the substrate was catalysed by PAHX. Both pro- and mature- forms of PAHX were fully active.